New findings into the genetic population structure of two commercially valuable and threatened sharks, Mustelus mustelus (Linnaeus, 1758) and M. punctulatus (Risso, 1827), allow refining management strategy in the Central Mediterranean Sea - Barbato, Matteo; Bonanomi, Sara; Borme, Diego; Ćetković, Ilija; Colloca, Francesco; Di Lorenzo, Manfredi; Marino, Ilaria A. M.; Mazzoldi, Carlotta; Pešić, Ana; Sala, Antonello; Zane, Lorenzo; Mezzavilla, Massimo (Frontiers in Marine Science, 2025)
Elasmobranch species are the direct or accidental catch of fisheries and can have a commercial importance. In the Mediterranean Sea, a long-term period of overfishing brought several demersal elasmobranchs to be depleted and threatened by extinction, due to vulnerability related to their life history traits. In such exploited species, information on genetic diversity and connectivity is lacking and should be collected to identify management units. In this study, we focused on two threatened smooth-hound species, Mustelus Mustelus (Linnaeus, 1758) and M. punctulatus (Risso, 1827), whose abundance and distribution showed a decline at the Mediterranean regional level in the last century. Thanks to an opportunistic yet extensive sampling, we obtained the largest subregional collection of specimens for genetic analysis so far. In total, 86 and 214 specimens of M. mustelus and M. punctulatus were collected between 2016 and 2020 in the Adriatic Sea and the Strait of Sicily. We assessed the population genetic structure typing 17 microsatellites and sequencing part of the mitochondrial control region in both species. We observed a substantial nuclear and mitochondrial genetic structure when accounting for the geographical sampling area for both species. Our results indicate the presence of at least two genetic stocks for each of the two species: one in the Strait of Sicily and the other in the Adriatic Sea. This study provides valuable data that should be integrated into a broader approach to define management units, improving the development of an effective management strategy for these threatened species in the Central Mediterranean Sea.